Active surveillance of paratuberculosis in Alpine-dwelling red deer (Cervus elaphus) - Filippi, Anita; Garbarino, Chiara; Nava, Matteo; Russo, Simone; Soares Filipe, Joel Fernando; Bianchi, Alessandro; Corlatti, Luca; Gugiatti, Alessandro; Buccheri Pederzoli, Clelia; Pigoli, Claudio; Pedrotti, Luca; Arrigoni, Norma; et al. (Frontiers in Veterinary Science, 2024)
Paratuberculosis (Johne's disease) is a globally widespread infectious disease affecting domestic and wild ruminants, caused by Mycobacterium avium subsp. paratuberculosis (MAP). The bacterium is excreted in the faeces and is characterized by high environmental resistance. The new Animal Health Law (Regulation EU 2016/429) on transmissible animal diseases, recently in force throughout the European Union, includes paratuberculosis within the diseases requiring surveillance in the EU, listing some domestic and wild Bovidae, Cervidae and Camelidae as potential reservoirs. Taking advantage of a culling activity conducted in the Stelvio National Park (Italy), this study investigated MAP infection status of red deer (Cervus elaphus) between 2018 and 2022, and evaluated the probability of being MAP-positive with respect to individual and sampling-level variables. A total of 390 subjects were examined macroscopically and tested for MAP, using different diagnostic tools: IS900 qPCR, culture, histopathology and serology. Twenty-three of them were found positive for MAP by at least one test, with an overall prevalence of 5.9% (95% CI 4.0-8.7), that respectively ranged from 12.4 % in the first culling season to 2.0 and 2.1% in the 2019-20 and 2021-22 culling seasons. Quantitative PCR assay on ileocecal valve and mesenteric lymph nodes detected the highest number of MAP positive animals. The results of the study showed the increased probability of being MAP-positive with increasing age and that red deer with lower body mass values were more likely to be infected with MAP. Overall, the absence of signs of clinical paratuberculosis and gross lesions together with the low level of shedding witness early phases of the disease among the positive red deer and support an improvement of the paratuberculosis status of this population, as shown by the decreased prevalence of the disease over the years.